Perancangan Pengendalian Bahaya Pada PT. Temprina Media Grafika - Garry Owen; I Nyoman Sutapa (Jurnal Titra, 2023)
PT. Temprina Media Graphic is a company engaged in the field of packaging and printing. There have been several work accidents at the production site of PT. Graphic Media Temprina. This final project was carried out using direct observation methods and interviews with factory heads, local staff and workers. The purpose of this final project is to reduce the number of work accidents at PT. Graphic Media Temprina. From the results of the analysis, 9 activities have been found in the production process that have high and medium risk analysis values and can cause work accidents. 28 risk control proposals have been proposed which are dominated by administrative controls and Personal Protective Equipment. The proposal given by the author has been approved by the company. It is predicted that some of the risk ratings of the activities will be low, but some are still the same.